KETAHANAN KAYU MANGIUM (Acacia mangium Willd.) TERHADAP SEBELAS JAMUR PELAPUK KAYU - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 2002)
Fungi resistance of 5, 8 and 11 year old sap and heart Acacia mangium Willd wood, taken from Parungpanjang (West Java Province) and Serang (Banten Province) were evaluated using modified DIN 52176 standard. The result showed that wood samples from Parungpanjang was classified as moderately resistant to resistant (class III-II), while those from Serang district as non resistant (class IV). Both the sap and heart wood had similar resistance (i.e. class III). The percentage of the weight loss of the heart wood was lower than that of the sap wood. The lowest weight loss was found on 11 year old samples, taken from Parungpanjang district. The highest weight loss was found on 8 year old samples from the same area and on 11 year old samples from Serang. The most virulent fungus was Coriolus versicolor followed by Tyromyces palustris, Polyporus sp. HHB-209, Pycnoporus sanguineus HHB-324, Schizophyllum commune HHB-204, Postia placenta. The less virulent ones were Dacryopinax spathularia, Chaetomium globosum, Pycnoporus sanguineus HHB-8149, and Phlebia brevispora The highest weight loss was recorded on the sap wood of 8 year old samples from Parungpanjang exposed to Lentinus lepideus culture, the lowest was on the heart wood (from the trees of the same age and origin) exposed to D. spathularia culture. The resistance of wood could be affected by the tree-growth site, age, position in the log, species and strain of fungi